Science self-efficacy and meta-variables as correlates of academic performance of students in biology - Achor, Emmanuel Edoja; Odoh, Comfort Ojela; Omale, Moses Ojochogwu (American Journal of Education and Learning, 2025)
This study examined the relationship between science self-efficacy, meta-variables (meta-awareness, meta-regulation, meta-monitoring, and meta-evaluation), and students’ academic performance in Biology among secondary school students in Kogi East, Nigeria. Six research questions and six null hypotheses were tested at a 0.05 significance level. The study adopted a correlational design. The population included 9,001 Senior Secondary Two students, with a sample of 382 selected from five schools using a multistage sampling technique. Data were collected using the researcher-designed Biology Performance Test (BPT), Biology Self-Efficacy Scale (BSES), and Biology Meta-Variable Scale (BMVS). These instruments were validated by experts in science education, measurement, and evaluation, and were trial tested. The reliability coefficients were 0.84 (BPT), 0.89 (BMVS), and 0.82 (BSES). Regression analysis addressed research questions, while ANOVA tested the hypotheses. Results indicated a strong correlation (r = 0.777, R² = 0.604) between science self-efficacy and biology performance. Meta-awareness (r = 0.650, R² = 0.423), meta-regulation (r = 0.677, R² = 0.458), meta-monitoring (r = 0.511, R² = 0.261), and meta-evaluation (r = 0.571, R² = 0.326) correlated significantly with biology performance.The combined influence of science self-efficacy and meta-variables on Biology performance (r = 0.510, R² = 0.260) was also significant. Findings suggest that higher science self-efficacy enhances academic performance in Biology. Meta-variables play a crucial role in shaping students’ learning outcomes. The study recommends improving Biology instruction through active engagement methods such as problem-solving tasks, group discussions, and real-world applications. Encouraging scientific investigations along with inquiry-based learning can further enhance students’ performance in Biology.